Aspects of nutritional knowledge, attitudes and practices of nurses working at the surgical division at the Kenyatta National Hospital, Kenya - Kobe, Judith A. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Human Nutrition))--University of Stellenbosch, 2006.